2021
DOI: 10.1177/0954406221992798
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and dynamic analysis of spiral bevel gear coupled system of intermediate and tail gearboxes in a helicopter

Abstract: The coupled dynamic model of the intermediate and tail gearboxes’ spiral bevel gear-oblique tail shaft-laminated membrane coupling was established by employing the hybrid modeling method of finite element and lumped mass. Among them, the dynamic equation of the shaft was constructed by Timoshenko beam; spiral bevel gears were derived theoretically by the lumped-mass method, where the effects of time-varying meshing stiffness, transmission error, external imbalance excitation and the like were considered simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The steps for modeling the SISs using MATLAB are listed below. [55][56][57] (a) The structure is discretized based on the local coordinate system, and the element stiffness matrix Κ e , element mass matrix M e , and external excitation matrix P e are determined. When building the plane frame model, the beams are assumed to be Euler-Bernoulli beams, in which the shear deformation is not considered.…”
Section: Direct Integration Methods Using Matlabmentioning
confidence: 99%
“…The steps for modeling the SISs using MATLAB are listed below. [55][56][57] (a) The structure is discretized based on the local coordinate system, and the element stiffness matrix Κ e , element mass matrix M e , and external excitation matrix P e are determined. When building the plane frame model, the beams are assumed to be Euler-Bernoulli beams, in which the shear deformation is not considered.…”
Section: Direct Integration Methods Using Matlabmentioning
confidence: 99%
“…As shown in Figure 5 is the jth bearing-housing element, one end node of the bearinghousing element is at the midpoint of the bearing, and the other end node is at the housing node, that is, at the center hole of the bearing seat. The bearing stiffness matrix K j b can be expressed as equation (9). Most of the coupled stiffness of bearings is very small, and the calculation equation only retains the main stiffness k xx , k yy , k zz , k uxux , k uyuy .…”
Section: Subsystem Modelmentioning
confidence: 99%
“…Papers by Walha et al, 6 Raclot and Velex, 7 and Shen et al 8 studied the two-stage spur gear system, and found the coupled vibration effect. Zhu et al 9 established the coupled dynamics model of the middle and tail gearboxes of the helicopter. They found that the diaphragm coupling has a significant effect on the vibration response of the coupling system.…”
Section: Introductionmentioning
confidence: 99%
“…5 As shown in Figure 1, the TDSS of an armed helicopter is composed of horizontal tail drive system, intermediate gearbox, oblique tail shaft system, tail gearbox, etc. 6,7 The horizontal tail drive shaft system (HTDSS) is the longest part of the TDSS and is the most likely to be shot by a bullet. When performing military missions, the tail drive shaft (TDS) extends from the fuselage to the tail rotor, which is particularly exposed during hovering.…”
Section: Introductionmentioning
confidence: 99%